2015
DOI: 10.2340/00015555-2130
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Drug Survival of Methotrexate and Acitretin in Patients with Psoriasis

Abstract: Drug survival has recently become an important clinical issue in psoriasis. However, there has been little research into factors associated with drug survival of methotrexate and acitretin. The aim of this study was to investigate factors associated with drug survival of methotrexate and acitretin treatment for psoriasis. Survival analysis was performed in patients who received methotrexate or acitretin for the treatment of psoriasis, drawn from the Clalit Health Services database. Investigated factors include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
40
3
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 31 publications
12
40
3
6
Order By: Relevance
“…The median drug survival was 1·8 years and 15% of patients remained on methotrexate after 5 years . This is similar to the previously published studies on this subject . The majority of patients discontinued methotrexate due to side‐effects.…”
supporting
confidence: 87%
“…The median drug survival was 1·8 years and 15% of patients remained on methotrexate after 5 years . This is similar to the previously published studies on this subject . The majority of patients discontinued methotrexate due to side‐effects.…”
supporting
confidence: 87%
“…The studies conducted by Shalom et al . ( n = 3,624; Israel), Arnold et al . ( n = 63; Switzerland), and Dávila‐Seijo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Drug survival, which usually correlates well with drug adherence, is another topic of interest in psoriasis as it can reflect its cost‐effectiveness . Drug adherence is the extent to which patients take medications as prescribed, whereas drug survival indicates the length of time a certain drug is in use until its cessation . Data regarding the drug survival of acitretin in psoriasis are summarized in Table .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies on factors associated with drug survival of conventional systemic treatment. It has been shown that comorbidities are a predictor for discontinuation of treatment and that lack of folic acid supplementation in patients treated with methotrexate is associated with treatment dropout [13] .…”
Section: Discussionmentioning
confidence: 99%